On Site Evaluation of a Tubular Microbial Fuel Cell Using an Anion Exchange Membrane for Sewage Water Treatment - Sugioka, Mari; Yoshida, Naoko; Iida, Kazuki (Frontiers in Energy Research, 2019)
This study evaluated the performance of a tubular microbial fuel cell (MFC) having a core of air-chamber wrapped with an anion exchange membrane in sewage wastewater treatment. Three MFCs were vertically assembled into one module and floated in sewage water channels before and after the treatment in primary sedimentation tank. The two MFC-modules showed almost similar electricity production in the range of 1.3–5.7 Wh·m-3-MFC, while the bottom MFCs (60–90 cm) showed a decrease in electricity than the top MFC (0–30 cm) and the middle MFC (30–60 cm). One of the MFC modules was then evaluated for the COD removal rate with two external resistances of 27 and 3, in a chemostat reactor (MFC:reactor = 1:5, v/v) under three hydraulic retention times (HRTs), 3 h, 6 h, and 12 h. The best COD removal rate of the MFC (COD-RTMFC), 54 ± 14% and BOD removal rate, 37 ± 17%, were observed with 3 of resistance and 12 h of HRT, resulting in 3.8 ± 2.0 A·m-3 of current recovery and 15 ± 7.5 % of Coulombic efficiency. Electricity generation efficiency (EGEMFC) was the best with 27 of resistance and 12 h of HRT and accounted for 0.18 ± 0.11 kWh·kg-COD-1 with 17 ± 6.4 % of COD-RTMFC and 0.65 ± 0.10 Wh·m-3 electricity production. Based on the calculation using the COD-RTMFC and EGEMFC, wastewater treatment can reduce electricity consumption by 55% via integration of the MFC treatment prior to the aeration.